“Each one of us did the best we could for the community, while also supporting each other”: community residents’ perspectives on community health worker (CHW) response during the COVID-19 pandemic - a community science worker-led qualitative study - Melina Michelen; Beatriz Lopez Galeana; Salvador Zárate; Sora Park Tanjasiri; Lindsay Donaldson; Patricia J. Cantero; Noraima Chirinos; Rocio Salazar; Mary Anne Foo; Samantha Peralta; Pilar Lara de Cortez; Guadalupe Capistran; et al. (BMC Public Health)
Abstract Background The COVID-19 pandemic significantly disrupted the health and social wellbeing of the United States population, disproportionately affecting low-income, immigrant communities of color. In Orange County, California, community health workers (CHWs) were essential to addressing multilevel community needs among impacted communities. However, little is known about how communities and CHWs responded to meet their needs amid pressing challenges. Methods CHWs completed a popular education qualitative methods program under a Community Science Worker (CSW) model to design and facilitate four semi-structured focus groups and three interviews with 32 residents in Orange County, California, to understand their pandemic experiences and interactions with CHWs. Sessions were recorded, transcribed, and analyzed using an adapted flexible coding approach to derive data-driven themes. Results Residents described how they supported one another, advocated for their communities, and fostered livelihood and resilience. Four main themes detail the community’s response: (1) facing a chain of interconnected challenges; (2) connecting with CHWs and accessing the services they facilitated; (3) fostering a community of care, a mutuality often inspired by interactions with CHWs; and (4) reinforcing foundations through a whole-of-community approach, including strengthening social policies. Conclusions Engaging community members is crucial for comprehensively understanding the CHW model. Given the enormous ongoing community challenges post-pandemic, these findings call for increased CHW presence, additional support and resources for health and socioeconomic needs, and improved information dissemination to bolster community resilience. Findings center mutual aid, emphasizing the importance of supporting communities in this crucial work. Additionally, engaging with residents who CHWs supported is vital for understanding the full impact of CHW models.